Buffered versus Non-Buffered Local Anesthesia in Septorhinoplasty: A Comparative Assessment of Injection Pain and Patient Satisfaction - Munir Abdulmoula; Omar Danfour; Mouna Abujazia; Ahmed Aniba; Fathi Abulifa (AlQalam Journal of Medical and Applied Sciences, 2025)
Rhinoplasty is among the most common facial aesthetic procedures. Although general anesthesia is the conventional standard, local anesthesia offers significant benefits, such as diminished intraoperative bleeding and expedited postoperative recovery. A primary limitation to its broader implementation is the pain associated with the injection of local anesthetics. This study aimed to assess the efficacy of buffering local anesthetic solutions with sodium bicarbonate in reducing the intensity of injection pain and enhancing patient comfort during septorhinoplasty performed under local anesthesia. A prospective, within-subject comparative study was conducted involving 20 patients who underwent elective septorhinoplasty. Each patient received two anesthetic formulations injected into the contralateral sides of the nose: a buffered solution (Solution A: pH 7.2-7.4, with sodium bicarbonate 7.5%) and a standard, non-buffered solution (Solution B: pH 4.5-5.5). The primary outcome measures were patient-reported pain perception during injection, time to anesthetic onset, duration of anesthetic effect, and intraoperative hemostatic quality. Buffered anesthesia was associated with a statistically significant reduction in injection pain, as reported by 18 patients (90%) (p < 0.001). The mean pain score for the buffered solution was 2.8 ± 1.4, compared to 5.7 ± 1.9 for the non-buffered solution, constituting a 51% reduction. A non-significant trend toward a faster onset of anesthesia was observed with the buffered solution (8.4 ± 2.6 minutes vs. 10.1 ± 3.4 minutes, p = 0.09). No statistically significant differences were identified between the two solutions regarding the duration of anesthesia (178 ± 24 minutes vs. 182 ± 27 minutes, p = 0.62) or hemostatic efficacy. The buffering of local anesthetics with sodium bicarbonate significantly attenuates injection-related pain in patients undergoing septorhinoplasty, without compromising anesthetic duration, hemostatic quality, or safety. The adoption of this technique is recommended to optimize patient comfort in rhinoplasty procedures utilizing local anesthesia.